Strategies for implementing music-based interventions for people with dementia: A systematic review. (17th December 2021) - Amano, Takashi; Strong, Joe; Hooley, Cole; Inoue, Megumi
Abstract: Previous research has found that music-based interventions are effective at improving several outcomes related to dementia for nursing home residents. Some studies have investigated the implementation of music-based interventions. However, to date, there is no synthesis available regarding strategies and outcomes of these implementation studies. This study aims to synthesize available evidence regarding implementation strategies and outcomes of music-based interventions for nursing home residents with dementia. We conducted a systematic literature search in PsychInfo, PubMed, MEDLINE, CINAHL, and The Cochrane Library. A total of 8 studies were included for the qualitative synthesis. Of the eight studies, half were studies of music therapy and the other half were on individualized music. We identified 49 implementation strategies. The most frequently reported category of strategies was planning (34.7%), followed by education (24.5%), quality management (24.5%), restructuring (12.2%), and finance (4.1%). No strategies under the category of attending to the policy context were reported. We identified 21 implementation outcomes. The most frequently reported category was adoption (33.3%), followed by fidelity (28.6%), appropriateness (19.0%), sustainability (9.5%), acceptability (4.8%), and cost (4.8%). No studies measured feasibility or penetration. Although various implementation strategies have been utilized, most of them are under the categories related to intervention methods. Less attention has been paid to strategies that aim at structural changes of intervention delivery systems. Future studies should investigate facilitators and barriers of implementing music-based interventions especially focusing on organizational and structural aspects.